Estimating crop yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A programme which evaluates the effects of climate and environment on agricultural production has now been operating for two years. ESPACE is designed to estimate the expected harvests of main food crops before the end of the rainy season. By...